Bencana dalam Konteks Spiritualitas Islam - Ahmad . (STAI Syaichona Moh. Cholil Bangkalan, 2018)
Natural disasters are extraordinary events that occur in the universe. Starting from floods, landslides, hurricanes, volcanic eruptions, earthquakes and tsunamis. Scientifically, natural disasters occur because of an imbalance in the universe. While according to the religious perspective, disasters occur due to the actions of humans who commit many sins. Natural disasters can occur as a form of examination (mihnah), reply (‘iqob), disaster (bala') or also as a torment (doom) the wrath of the Creator on his servant. In the Qur'an and Hadith, the disaster that befalls humanity is more caused by sinful acts and lawlessness. The former people got the punishment because they did not believe in God and denied the messengers who had been sent down to them and did arrogant and dhalim. However, in today's context, humans do not ensure that natural disasters that afflict a region (clan) are surely doom. Likewise, it cannot be ascertained that humans who are victims of disasters are disobedient humans. This is because those who are also victims include pious people.